Comparison of Anterior Cruciate Ligament Reconstruction With Versus Without Anterolateral Augmentation: A Systematic Review and Meta-analysis of Randomized Controlled Trials. Issue 3 (31st March 2023) - Lai, Sike; Zhang, Zhong; Li, Jian; Fu, Wei-Li
Background: It is clear that the anterolateral ligament has an important role in rotational knee stability. However, whether patients undergoing anterior cruciate ligament (ACL) reconstruction (ACLR) can benefit from anterolateral augmentation (ALA) is still controversial. Purpose: To compare the effects of isolated ACLR versus ACLR combined with ALA (ACLR+ALA) on clinical outcomes and knee stability. Study Design: Systematic review; Level of evidence, 1. Methods: The methodology followed PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. A literature search of the PubMed, Embase, and Cochrane Library Central Register of Controlled Trials databases was undertaken to identify all randomized controlled trials (RCTs) comparing isolated ACLR with ACLR+ALA for the treatment of ACL injuries in the last 15 years. The Cochrane Collaboration risk-of-bias tool and the revised Jadad scale were utilized by 2 independent reviewers to determine the quality of RCTs. Relevant data were extracted and compared between procedures, and heterogeneity across the RCTs was assessed using the I 2 statistic. Results: The initial search yielded 849 articles. A total of 14 studies (1850 patients; 941 ACLR and 909 ACLR+ALA) satisfied the eligibility criteria for the meta-analysis. There were no significant differences between the procedures in terms of patient-reported outcomes (International Knee Documentation Committee score, Tegner score, Knee injury and Osteoarthritis Outcome Score) or return-to-sport rates. However, patients who underwent ACLR+ALA had better knee stability based on the pivot-shift test (risk ratio [RR], 1.06 [95% CI, 1.02 to 1.10]; P = .0008), Lachman test (RR, 1.03 [95% CI, 1.00 to 1.07]; P = .04), and side-to-side difference in anterior laxity (standardized mean difference, –0.55 [95% CI, –0.98 to –0.12]; P = .01) as well as a lower incidence of graft failure (RR, 0.30 [95% CI, 0.19 to 0.45]; P < .01) compared with patients who underwent isolated ACLR. Conclusion: ALA can be considered as a reinforcement of ACLR to improve anteroposterior and anterolateral rotational stability of the knee and reduce the risk of failure. The patient-reported outcomes of isolated ACLR were similar to those of ACLR+ALA, and both procedures provided improved knee function.